Doing landscape : sensorial and artistic approaches to Donkalnis and Spiginas Mesolithic–Neolithic ritual sites in western Lithuania - Ahola, Marja; Lassila, Katri; Mannermaa, Kristiina (Taylor and Francis Ltd., 2024)
During the Mesolithic and Neolithic, foragers dwelling in the Eastern Baltic, Scandinavia and Fennoscandia regions buried some of their dead on lake islands or other coastal sites. Based on ethnographic accounts, these sites are often understood as liminal places where water separates the lands of the dead and the living. In this paper, we take a more relational view of place and suggest that a particular combination of spatial perception of landscape and the dynamic nature of coastal sites might have contributed to the social agency of these places, resulting in their use as places for ritual activity. By exploring two Mesolithic–Neolithic burial places, Donkalnis and Spiginas (western Lithuania), with sensory archaeological and artistic approaches, we suggest that the ancient foragers of this region buried human bodies in these locations to be part of the place itself. Similar to other depositional acts, this could have been done to mark the location or communicate with the surrounding world. Peer reviewed